"The lottery of my life": Migration trajectories and the production of precarity among Bangladeshi migrant workers in Singapore's construction industry. (September 2018) - Baey, Grace; Yeoh, Brenda S. A.
Within the scholarship on precarity, low-waged contract-based migrants are recognized as centrally implicated in precarious employment conditions at the bottom of neoliberal capitalist labor markets. Precarity as a socially corrosive condition stems from both the multiple insecurities of the workplace as disposable labor, and a sense of deportability as migrant subjects with marginal socio-legal status in the host society. Our study of Bangladeshi construction workers in Singapore contributes to refining understandings of precarity by approaching labor migration as a cumulative, intensively mediated process, whereby risks and vulnerabilities are compounded across different sites in migrants' trajectories, even as they enact themselves as mobile, aspiring subjects. As a condition-in-the-making, precarity is experienced and compounded, through a continuum beginning in pre-migration indebtedness, multiplying through entanglements with the migration industry, and manifesting in workplace vulnerabilities at destination. It is most finely balanced when predictability and planning yield to arbitrary hope.